Socioeconomic inequalities and family planning utilization among female adolescents in urban slums in Nigeria - Akinyemi, Akanni Ibukun; Ikuteyijo, Olutoyin Opeyemi; Mobolaji, Jacob Wale; Erinfolami, Temitope; Adebayo, Samuel O. (Frontiers in Global Women's Health, 2022)
Family planning (FP) utilization is important for preventing unwanted pregnancy and achieving optimal reproductive health. However, the modern contraceptive prevalence rate (mCPR) among women of childbearing age is still low in many low- and middle-income countries (LMIC), particularly in Nigeria, despite interventions to increase access and utilization. The low mCPR has been associated with a high prevalence of unwanted pregnancy, unsafe abortion, sexually transmitted infections such as HIV/AIDS, and high maternal and infant mortality in LMIC. This study examines the role of socioeconomic inequality on family planning utilization among female adolescents of various ethnic backgrounds in urban slums in Nigeria. Methods The study utilized data from the Adolescents Childbearing Survey (2019). A total sample of 2,035 female adolescents of ages 14-19 years who were not pregnant at the time of the study and resident in selected slums. Associations between socioeconomic inequalities – measured by wealth index, social status and education – and modern contraceptive use were examined using relative and slope inequality indices, and logistic regression models. Results The results show that only 15% of the female adolescents in the North, and 19% in the South reported mCP use. While wealth index and education were important predictors of FP use among adolescents in southern urban slums, only education was important in the north. However, the relative and slope inequality indices further indicate that adolescents with no education and those in the lowest social status use more fewer contraceptives compare to their counterparts with higher wealth and social statuses . Those with secondary/higher education and the highest social status respectively were more disadvantaged in terms of FP utilization (Education: RII = 1.83, p<0.05; 95% C.I.=1.02 – 2.71; Social Status: RII = 1.97, p<0.05; 95% C.I.=1.26 – 2.68) with results showing a more marked level of disparity when disaggregated by north and south. Conclusion The persistent socioeconomic inequalities among female adolescents in Nigeria, especially those in the urban slums, have continued to limit their utilization. Policy measure in education, communication and subsidized contraceptives should be intensified for vulnerable female adolescents in the slums.